Attosecond time-resolved autoionization of argon - Wang, He; Chini, Michael; Chen, Shouyuan; Zhang, Chang-Hua; He, Feng; Cheng, Yan; Wu, Yi; Thumm, Uwe P. E.; Chang, Zenghu (My University, 2010)
Autoionization of argon atoms was studied experimentally by transient absorption spectroscopy with isolated attosecond pulses. The peak position, intensity, linewidth, and shape of the 3s3p[superscript 6]np [superscript 1]P Fano resonance series (26.6–29.2 eV) were modified by intense few-cycle near infrared laser pulses, while the delay between the attosecond pulse and the laser pulse was changed by a few femtoseconds. Numerical simulations revealed that the experimentally observed splitting of the 3s3p[superscript 6]4p [superscript 1]P line is caused by the coupling between two short-lived highly excited states in the strong laser field.
Keywords: Autoionization; Argon; Transient absorption spectroscopy; Electron correlation